Recent Advances in Biomaterials and Dental Disease - Kharouf, Naji; Sauro, Salvatore; Mancino, Davide (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The researchers involved in this reprint will continue their studies to improve the existent dental biomaterials in order to achieve optimal dental treatment with biocompatible, bioactive, and stable properties. As the Guest Editors, we sincerely value and thank the reviewers for their insightful comments and the support of the team at Bioengineering. Finally, we express our gratitude to all contributing authors for their valuable research. Altogether, the 16 research papers/reviews in this Special Issue entitled "Recent Advances in Biomaterials and Dental Disease" reflect the importance of in vitro and in vivo studies for improving the efficacy of using biomaterials in dental treatment.